Nonprofit marketing - Parsons, Elizabeth; Maclaran, Pauline; Tadajewski, Mark.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
This work addresses both the historical and conceptual development of the field of nonprofit marketing as well as the new concepts and challenges it faces in the new millennium.
v. 1. The evolution of nonprofit marketing -- v. 2. Nonprofit marketing -- v. 3. Key debates and contemporary issues in nonprofit marketing.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Nonprofit organizations -- Marketing; Electronic books